PENGARUH PENERAPAN SOP (STANDARD OPERATING PROCEDURE), SISTEM PENGHARGAAN (REWARD SYSTEM), PELATIHAN DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA PADA KARYAWAN PT. BPR WILIS JEMBER - Ellene Pricillia Budiarso; Suwignyo Widagdo (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2021)
This study aims to determine the effect of the application of SOP, reward system, training and work environment on employee work productivity at PT. BPR Willis Jember. The data used in this study are primary data obtained from respondents' responses to the questionnaire. Samples taken as many as 40 respondents with sampling techniques using probability sampling, namely by purposive sampling method. The data obtained is then processed using the SPSS analysis tool, this analysis includes validity test, reliability test, multiple linear regression analysis, classic assumption test, and statistical test through t test, F test and coefficient of determination (R2). The results of the study show that the factors of the application of SOP, reward systems, training and work environment simultaneously affect work productivity, whereas if partially the factors for the application of SOP and training have no significant effect on work productivity, but for reward system factors and work environments have a significant towards work productivity.